South Asians in the diaspora : histories and religious traditions - Jacobsen, Knut A., 1956-; Kumar, P. Pratap, 1952- (Studies in the history of religions, 2004)
This work deals with a phenomenon of increasing global significance, the South Asian diaspora. The case studies explore and analyze the social, religious and cultural reality of people in the diaspora belonging to Jainism, Buddhism, Hinduism, Christianity, Islam, and Sikhism.